2020
DOI: 10.1111/odi.13649
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol transmission for SARS‐CoV‐2 in the dental practice. A review by SIdP Covid‐19 task‐force

Abstract: Current evidence suggests that SARS-CoV-2, the virus that causes COVID-19, is predominantly spread from person to person. Aim of this narrative review is to explore transmission modality of SARS-CoV-2 to provide appropriate advice to stakeholders, in order to support the implementation of effective public health measures and protect healthcare workers that primary face the disease. "In vivo" and "in vitro" studies from laboratories and hospitals confirmed the presence of surface contamination and provided insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…Bruna et al [25] argued that the use of rubber dams should be mandatory, and Butera et al [26] minimized the use of aerosol-producing instruments, such as ultrasound and air, to reduce the production of highly polluted aerosols. It has been reported that it is necessary to promote the use of chlorhexidine, hydrogen peroxide, or povidone iodine; the development of new treatments, such as laser and ozone; and the administration of probiotics prior to each dental treatment [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Bruna et al [25] argued that the use of rubber dams should be mandatory, and Butera et al [26] minimized the use of aerosol-producing instruments, such as ultrasound and air, to reduce the production of highly polluted aerosols. It has been reported that it is necessary to promote the use of chlorhexidine, hydrogen peroxide, or povidone iodine; the development of new treatments, such as laser and ozone; and the administration of probiotics prior to each dental treatment [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the health environments that generate droplets and aerosols have received special attention in sanitary measures, due to the risk of cross-contamination, especially in the pandemic moment of Covid-19 [ 22 ]. With that in mind, in this present study, we simulated a situation of droplets and highly contaminated aerosols dispersion in a dental environment.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of bio-aerosol generation can be accomplished by using many protocols ( 26 , 29 ). In our experience, we followed two different approaches to control bio-aerosol generation: (1) the use of pre-operative mouthwash; and (2) the regulation of daily dental procedures ( 30 , 31 ). The use of pre-operative mouthwash (1% hydrogen peroxide, 0.2% povidone iodine, or alcohol free options such as 0.2% chlorhexidine rinse) has been shown to control the bacterial burden ( 23 ).…”
Section: Practice-based Clinical Challengesmentioning
confidence: 99%